Sports experience related bone tissue mineralization specifics in skiers - Kuchin, R. V.; Nenenko, N. D.; Chernitsyna, N. V.; Stogov, M. V.; Maksimova, T. A. (Theory and Practice of Physical Culture, 2019)
The paper is devoted to the study of the peculiarities of bone mineralization in skiers depending on their sports experience. Four Experimental Groups were formed: Group 1 (n=7) was made of the young males involved in cross-country skiing with 3-4 years of sports experience; Group 2 (n=8) - male cross-country skiers with 7-8 years of sports experience; Group 3 (n=7) - male cross-country skiers with 11-12 years of sports experience. The Control Group (n=9) involved the non-sporting young males. The young males of Group 1 were found to have a decrease in the total level of bone mineralization and bone mineral density as opposed to the Control Group. The young males of Groups 2 and 3 were observed to have an increase in mineralization of the lower limb bones and a decrease in that of the upper limb ones. In Groups 2 and 3, there was an increase in bone mineral density in the femur neck, diaphysis of femur, and lumbar vertebrae. Therefore, with growing sports experience, there occurs functional redistribution of bone minerals. The marked delay in bone mineralization among the young males involved in cross-country skiing requires nutritional correction with calcium supplements.